2019
DOI: 10.1109/access.2019.2949063
|View full text |Cite
|
Sign up to set email alerts
|

Optimal VMD-Based Signal Denoising for Laser Radar via Hausdorff Distance and Wavelet Transform

Abstract: Laser radar echo signals are easily contaminated by noise, such as background light and electronic noise, and this noise is an obstacle for the subsequent signal detection. However, the conventional denoising methods cannot achieve satisfactory effects when the signal-to-noise-ratio (SNR) is ultralow. In this paper, a novel denoising method for laser radar echo signals based on the parameter-optimal variational mode decomposition (VMD) combined with the Hausdorff distance (HD) and wavelet transform (WT) is pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…In this study, the denoising process using wavelet decomposition and thresholding method is performed to improve the quality of the DCG signal. Although there are many studies of the denoising process using the wavelet function [ 35 , 72 , 73 , 74 ], to the best of the author’s knowledge, previous studies have yet to provide the optimal mother wavelet selection for the DCG signal. The purpose of this study is proposing the optimal selection of the mother wavelet function and the decomposition level for the DCG signal to optimize the performance of the denoising process.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the denoising process using wavelet decomposition and thresholding method is performed to improve the quality of the DCG signal. Although there are many studies of the denoising process using the wavelet function [ 35 , 72 , 73 , 74 ], to the best of the author’s knowledge, previous studies have yet to provide the optimal mother wavelet selection for the DCG signal. The purpose of this study is proposing the optimal selection of the mother wavelet function and the decomposition level for the DCG signal to optimize the performance of the denoising process.…”
Section: Discussionmentioning
confidence: 99%
“…From (11), (12), (13) and (14), it can be concluded that a subset of fault signatures providing both large value of ( ), This means that the algorithm explores an optimal feature vector which yields the best feature space of categories to categorize by the classifier in the following stage.…”
Section: Ga-based Fault Feature Selectionmentioning
confidence: 99%
“…Another alternative approach, currently outperforming former methods, is a wavelet threshold-based de-noising method. However, this method still faces difficulties in choosing a proper threshold, and sometimes is incapable of resolving overlapping frequencies [11][12][13]. Empirical mode decomposition (EMD), a cutting-edge method with compelling noise-reducing capabilities, is another potential option, especially for vibration signal noise.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the method based on EMD, it has a solid mathematical theoretical foundation, and it can avoid the error accumulation phenomenon. VMD-based denoising methods have been used in many fields, such as underwater acoustic signal [22], ship-radiated noise [23], seismic signal [24], and laser radar [25]. It is worth noting that the key problem of signal denoising with VMD is the determination of the mode number K and relevant modes.…”
Section: Introductionmentioning
confidence: 99%